Optical study on the combustion characteristics and soot emissions of diesel–soybean biodiesel–butanol blends in a constant volume chamber. Issue 4 (November 2016) - Qi, D.H.; Chen, B.; Zhang, D.; Lee, C.F.
Abstract: To investigate the effects of ambient temperature on the combustion characteristics, and soot formation and oxidation, a detailed comparative study between two different volumetric diesel–soybean biodiesel–butanol blended fuels was carried out in an optical constant volume combustion chamber. The volumetric ratios were the 80% diesel/15% soybean biodiesel/5% butanol denoted as S15B5 and 80% diesel/10% soybean biodiesel/10% butanol denoted as S10B10 and were tested in this study with different ambient temperatures (from 800 K to 1200 K) at the start of injection. Experimental results indicated that the ignition delays of the two blended fuels were almost identical, and S15B5 fuel presented higher maximum cumulative heat release, heat release rate and combustion pressure compared to those of S10B10 fuel. With the increase of ambient temperature, the flame propagated downstream of the spray jet and became brighter. The soot distribution was also increased at the downstream of the spray jet with a higher ambient temperature for both blended fuels, and S10B10 had a lower value of normalized time-integrated soot mass (NTISM). Therefore, S10B10 had more advantages to reduce the soot emission compared to S15B5 fuel. Also, increasing the ambient temperature from 800 K to 1200 K led to a rapid decrease in the value of NTISM for both blended fuels. Highlights: Combustion characteristics and the soot formation and oxidation were study in a constant volume combustion chamber. Combustion pressure and heat release rate were increased with the decrease of ambient temperature. Natural flame luminosity becomes brighter with the increase of ambient temperature. Soot distribution was near the wall region at low temperature, and formed downstream of the spray jet at high temperature. S10B10 fuel exhibited more advantages to reduce the soot emission compared to S15B5 fuel.